Soil Organic Carbon in Forest and Other Land Use Types at Bengkulu City, Indonesia - Wiryono; Zainal Muktamar; Deselina; Steffanie Nurliana; Hastari Aningtias; Paka Mutiara Anugrah (Jurnal Manajemen Hutan Tropika, 2021)
Conversion of natural forest into agricultural land uses has decreased soil organic carbon (SOC) and increased carbon emission into the atmosphere, but proper management of agricultural land can sequester carbon from the atmosphere and increase the SOC. This study was conducted to estimate the SOC content and storage in a forest, agroforestry land, oil palm plantation, and agricultural experimental field and to analyze the correlation between the SOC and other soil characteristics at Bengkulu City, Indonesia. Soil were sampled from the following depths: 0–10 cm, 10–20 cm, and 20–30 cm. The biomass of litter and ground cover was also sampled. This study found that the forest had the highest average SOC content from the three depths, and 0–30 cm depth SOC storage, while the agroforestry system had the lowest of both SOC content and storage. The 0–10 cm depth had the highest SOC content and storage, while the 20–30 cm depth had the lowest of both variables. The SOC was positively correlated with litter biomass, field capacity, exchangeable potassium, cation exchange capacity, and negatively correlated with bulk density and exchangeable calcium, but not correlated with total nitrogen and available phosphorus. High litter biomass input is the key to the maintenance of high SOC.